Lower-body power, linear speed, and change-of-direction speed in division I collegiate women`s volleyball players - Lockie, R. G.; Dawes, J. J.; Callaghan, S. J. (Biology of Sport, 2020)
Volleyball players need to sprint and change direction during a match. Lower-body power, often measured by jump tests, could contribute to faster movements. How different jumps relate to linear and change- of-direction (COD) speed has not been analyzed in Division I (DI) collegiate women`s volleyball players. Fifteen female volleyball players completed the vertical jump (VJ), two-step approach jump (AppJ), and standing broad jump (SBJ). Peak power and power-to-body mass ratio (P:BM) were derived from VJ and AppJ height; relative SBJ was derived from SBJ distance. Linear speed was measured via a 20-m sprint (0-10 and 0-20 m intervals); COD speed was measured using the pro-agility shuttle. Pearson`s correlations (p < 0.05) calculated relationships between the power variables, and speed tests. There were no significant relationships between the power variables and the 0-10 m sprint interval. Greater VJ height (r = -0.534) and P:BM (r = -0.557) related to a faster 0-20 m sprint interval. This be due to a greater emphasis on the stretch-shortening cycle to generate speed over 20 m. However, although a 20-m sprint may provide a measure of general athleticism, the distance may not be specific to volleyball. This was also indicated as the AppJ did not relate to any of the speed tests. Nonetheless, VJ height and P:BM, and SBJ distance and relative SBJ, all negatively correlated with the pro- agility shuttle (r = -0.548 to -0.729). DI women`s collegiate volleyball players could develop absolute and relative power in the vertical and horizontal planes to enhance COD speed.